2022
DOI: 10.3389/fphar.2022.859167
|View full text |Cite
|
Sign up to set email alerts
|

Wu-Mei-Wan Ameliorates Murine Ulcerative Colitis by Regulating Macrophage Polarization

Abstract: An increasing body of evidence shows that macrophages play an important role in the pathogenesis of ulcerative colitis (UC). Macrophage polarization and changes in related signaling pathways are reported to have a protective effect on intestinal inflammation. The well-known Chinese medicine Wumeiwan (WMW) has been used to treat diarrhea, one of the main symptoms of colitis, for more than 2,000 years. Increasing evidence shows that WMW can inhibit intestinal inflammation and repair damaged intestinal mucosa, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…52 In addition, it was found that an increased polarization of colonic macrophages from MO to M1 and a decreased M2 polarization caused by activation of the NF-κB pathway are potential causes of DSS-induced colitis, which is the mechanism by which the herbal Wu-Mei-Wan exerts its protective effect. 53 We found that the macrophage M1/M2 polarization imbalance occurred in the liver tissue of carp exposed to CPF, which was manifested by a significant upregulation of the M1-type marker expression and significant downregulation of the M2-type marker and that the imbalance could be reversed by Bai. The above results suggest that M1/M2 polarization of macrophages is a downstream effector process of the CPF-induced NF-κB pathway activation.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…52 In addition, it was found that an increased polarization of colonic macrophages from MO to M1 and a decreased M2 polarization caused by activation of the NF-κB pathway are potential causes of DSS-induced colitis, which is the mechanism by which the herbal Wu-Mei-Wan exerts its protective effect. 53 We found that the macrophage M1/M2 polarization imbalance occurred in the liver tissue of carp exposed to CPF, which was manifested by a significant upregulation of the M1-type marker expression and significant downregulation of the M2-type marker and that the imbalance could be reversed by Bai. The above results suggest that M1/M2 polarization of macrophages is a downstream effector process of the CPF-induced NF-κB pathway activation.…”
Section: Discussionmentioning
confidence: 75%
“…It was shown that miR-224-5p and PTX3 constitute a regulatory axis that promotes M1 macrophage polarization and, thus, bone and joint injury through activation of the p65/NF-κB pathway . In addition, it was found that an increased polarization of colonic macrophages from MO to M1 and a decreased M2 polarization caused by activation of the NF-κB pathway are potential causes of DSS-induced colitis, which is the mechanism by which the herbal Wu-Mei-Wan exerts its protective effect . We found that the macrophage M1/M2 polarization imbalance occurred in the liver tissue of carp exposed to CPF, which was manifested by a significant upregulation of the M1-type marker expression and significant downregulation of the M2-type marker and that the imbalance could be reversed by Bai.…”
Section: Discussionmentioning
confidence: 80%
“…Du et al ( Du et al, 2021 ) reported that Wumeiwan could reduce DAI and histopathological scores in the UC rats by inhibiting the inflammatory reaction. In DSS-induced acute colitis mice, Wumeiwan could increase the percentage of M2 macrophages and decrease the percentage of M1 macrophages, and significantly reduce the secretion of pro-inflammatory factors, including TNF-α, IL-1β, and IL-6, by inhibiting M1 macrophage polarization and increase the secretion of anti-inflammatory factors, including IL-10, Arg-1, and TGF-β1, in colon tissues by promoting M1 macrophage polarization ( Yan et al, 2022 ).…”
Section: Tcm Alleviates Uc By Regulating Macrophage Polarizationmentioning
confidence: 99%
“…Xiong et al ( Xiong et al, 2021 ) reported that berberine could inhibit M1 polarization and promote M2 polarization in colonic macrophages, improve the intestinal inflammatory environment, and relieve colitis by inhibiting the NF-κB signaling pathway. Yan et al ( Yan et al, 2022 ) study found that Wumeiwan could inhibit M1 macrophage polarization and promote M2 macrophage polarization by inhibiting the activation of the NF-κB signaling pathway, thereby inhibiting inflammatory responses and alleviating colonic tissue damage in DSS-induced colitis.…”
Section: The Potential Mechanisms Of Macrophage Polarization Regulate...mentioning
confidence: 99%
See 1 more Smart Citation